Kebijakan Pemerintah Sebagai Solusi Meningkatkan Pengembangan UMKM di Masa Pandemi - Vina Natasya; Pancawati Hardiningsih (Ekonomis: Journal of Economics and Business, 2021)
This study aims to analyze the effect of providing social assistance, tax incentives, and expansion of working capital on the development of MSMEs during the Covid-19 pandemic. The research was conducted at UMKM West Semarang and Central Semarang. The population in this study were MSME actors who had taken advantage of tax incentives and received social assistance in West and Central Semarang 2. Purposive sampling was used to obtain a sample of 269 MSMEs. The research data were obtained as many as 56 observations carried out on a weekly basis from April to October 2020 using the documentary method. The analysis technique uses multiple linear regression to test the research hypothesis. The results showed that the provision of social assistance, tax incentives, and expansion of working capital affected the development of MSMEs during the Covid-19 pandemic. This research is based on testing through industrial attractiveness theory approach. The results of this study can provide additional information for the government in preparing a large scheme for economic protection and recovery programs for MSMEs affected by Covid-19 as well as evaluating the MSME business strategy towards a modern UMKM business model while maintaining health protocols.